User Interface Design Improvement and Usability Evaluation for Evolution Web Application of Telkom Indonesia Using User-centered Design - Faisal Adly Aditya Pradana; Mira Kania Sabariah; Monterico Adrian (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Evolution is a web application for collecting the Evidence report. This application is used regularly every quarter of the year. The main purpose is as a repository of evidence control that can be used at any time for audit purposes. Evolution Web Application will be utilized as a research object because there are problems with the user interface design and did not meet the concept of usability. To validate the Evolution Web Application User Interface Design problem and the improvements that will be applied according to user needs. User interview is conducted using Focus Group Discussion (FGD) with Evolution web Application users. The purposes of Focus Group Discussion (FGD) are to find problems in the user interface and expectations to achieve user goals for user interface design improvement. The interview results show that the current User Interface design has significant flaws. To improve the usability of the Evolution Web Application, a method known as User-centered Design (UCD) is used for improving the User Interface design of the Evolution Web Application. The evaluation after design improvement is carried out by using a Heuristic Evaluation involving 3 experts to review the usability of the design improvement result. Heuristic Evaluation produces answers from 3 experts with a severity value not more than a severity value of 2, which indicates a severity status of 2 is a Minor usability problem or fixing should be given low priority.